PERFECTION OF MARKETING ACTIVITY FOR A CONSTRUCTION COMPANY - I. Kogotkova; A. Mekhtieva (Вестник университета, 2016)
The article deals with the current state of the Russian marketing in the construction industry, the main problems and their causes, as well as a number of recommendations to improve the marketing activities of a construction company based on the specific problems.